THE INFLUENCE OF FINANCIAL MANAGEMENT FUNCTION TOWARDS COMPANY'S SKILLS AND VALUES IN INDONESIA’S CONSUMPTION GOODS INDUSTRY - Nurqamarani, Adisthy Shabrina; Jonathan, LCA. Robin; Militina, Theresia (Archives of Business Research, 2019)
This study aims to analyze and determine the effect of financial management functions in the form of investment decisions, funding decisions and dividend policies on profitability and corporate value in publicly listed companies within consumer goods industry in Indonesia during 2013-2015. The population of the consumer goods industry sector that went public (www.idx.co.id) was 37 issuers and examined the financial statements of 32 issuers that distributed dividends in 2013-2015. This research is a quantitative study of causality among several variables. The data used are cross section data and secondary data types in the form of financial reports published on the Indonesia Stock Exchange, literature and research from other parties. By using financial ratios related to financial management functions: investment decisions, funding decisions, dividend policy as an independent variable and profitability and firm value as the dependent variable, using path analysis assisted with the SPSS version 20, can be seen the magnitude of influence shown by the path coefficient on each path diagram of the causal relationship between the independent variables to the dependent variable. The results showed that the functions of financial management have a significant effect on profitability. Investment decisions and profitability of companies have a positive and significant effect on firm value, while funding decisions and dividend policies have no significant effect on firm value. Proficiency does not have a significant effect in mediating the functions of financial management on firm value. But in terms of probability, it helped strengthen the influence of financial management functions on corporate value.